Case report: metoclopramide induced acute dystonic reaction in adolescent CYP2D6 poor metabolizers - Fink, Franz-Martin; Bognar, Marta; Hengl, Petra; Paulmichl, Markus; Nofziger, Charity (Frontiers in Pharmacology, 2023)
Metoclopramide is indicated for the management of gastroesophageal reflux, gastric stasis, nausea and vomiting. Metoclopramide-induced dystonic reactions (MIADRs), along with repetitive involuntary protrusion of the tongue, are well-known phenomena in children and young adults that may appear after the first dose. The drug is primarily metabolized via oxidation by the cytochrome P450 enzyme CYP2D6, and to a lesser extent by CYP3A4 and CYP1A2. A recommendation to decrease metoclopramide dosing in patients with severely limited to no CYP2D6 activity (i.e. poor metabolizers, PMs) is contained within the drug label. It is important to note, however, that a requirement or recommendation for pre-emptive testing for CYP2D6 metabolizer status is not included in the drug label. We present two cases of acute dystonia in two nonconsanguineous male adolescents: one following metoclopramide and cimetidine administration in a 14 year old to treat gastroesophageal reflux, and another following metoclopramide and pantoprazole administration in a 17 year old with acute gastroenteritis. A retrospective pharmacogenetic analysis revealed both patients as CYP2D6 PMs.